Advanced metastatic breast carcinoma in sickle cell disease - Nwagu, Marcellinus uchechukwu; Thompson, Ologo; Oyekemi, Akinola (Faculty of Medicine, Trisakti University, 2019)
BackgroundBreast cancer is the leading cancer in women leading to over 400,000 deaths per year worldwide. It begins in the breast tissue and can metastasize to other organs if early diagnosis and treatment is not instituted. Women with sickle cell disease are usually spared from breast cancer and other solid tumours due to the tumoricidal effect of sickled erythrocytes. Breast cancers are rare among these group of patients. Despite its rare occurrence, this paper was to emphasize the need for breast cancer screening among female sickle cell disease patients who have positive family history of breast cancer.Case descriptionOO was a 30-year old woman with sickle cell disease who presented to the hospital one and half years ago with a seven months history of right breast swelling and pains. She had lost her mother to breast cancer about 15 years ago. Mammography and histology of breast biopsy confirmed diagnosis of invasive ductal carcinoma of the right breast. Financial constraint was a major challenge in managing this patient as she was unable to buy her chemotherapy. She developed features suggestive of metastasis such as seizures and hepatomegaly. She was stabilized and discharged home but we lost her to follow up. She died at home.ConclusionÂ Â Â Breast cancer is rare among females with sickle cell disease; any of them with a family history should be routinely screened for early diagnosis and treatment.